NASICON type solid electrolyte and preparation method and application thereof

Through Y3+ doping and specific sintering processes, the density and conductivity of the ceramic solid electrolyte are improved, the problems of poor sintering performance and low conductivity are solved, and high-performance solid electrolyte suitable for large-size batteries are achieved.

CN119695261APending Publication Date: 2025-03-25WUXI INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411879224.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing ceramic solid electrolytes have poor sintering performance and low ionic conductivity, making it difficult to meet the needs of large-sized batteries.

Method used

By doping Y3+ atoms, adjusting the lattice parameters and structural phase transition temperature, the Li1.3Al0.3-xYxTi1.7(PO4)3 (LAYTP-x) electrolyte is synthesized by conventional solid phase reaction, and its density and conductivity are improved through a specific sintering process.

Benefits of technology

It significantly improves the relative density and total conductivity of NASICON type solid electrolyte, reduces activation energy, and improves electrochemical performance. It is suitable for large-size solid lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695261A_ABST
    Figure CN119695261A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid electrolyte, and discloses NASICON type solid electrolyte as well as a preparation method and application thereof. The expression of the NASICON type solid electrolyte is Li < 1.3 > Al < 0.3-x > Y < x > Ti < 1.7 > (PO4) < 3 >, and x is more than 0 and less than or equal to 0.07. The obtained solid electrolyte has an NASICON type structure, and the Y element is uniformly distributed in the electrolyte. Wherein the relative density (95.8%) and the total conductivity (2.03 * 10 <-4 > S cm <-1 >) of the Li1. 3Al0. 27Y0. 03Ti1. 7 (PO4) 3 obtained in the embodiment 3 of the invention are the highest, and the activation energy of the Li1. 3Al0. 27Y0. 03Ti1. 7 (PO4) 3 is relatively low and is 0.33 eV. When the obtained Li1. 3Al0. 27Y0. 03Ti1. 7 (PO4) 3 is matched with an NCM811 high-voltage positive electrode, the obtained Li / LAYTP-0. 03 / NCM811 battery shows excellent electrochemical performance, specifically, after 50 times of circulation at 0.2 DEG C, the battery capacity reaches 155mAh g <-1 >, and the coulombic efficiency is about 100%, which indicates that the obtained Li1. 3Al0. 27Y0. 03Ti1. 7 (PO4) 3 electrolyte promotes the high reversibility of lithium ion intercalation / deintercalation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a NASICON solid electrolyte and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) have become the standard power source for mobile electronic devices such as electric vehicles, laptops, and mobile phones due to their high output voltage, high energy density, and low environmental pollution. However, the poor thermal stability of polyolefin separators and flammable and volatile organic electrolytes limit the development of lithium-ion batteries towards large-scale, high-energy, and high-safety. Compared with traditional lithium-ion batteries, solid-state batteries using solid electrolytes as separators and electrolytes have become the research focus of the next generation of battery systems. Among them, solid electrolytes, as the key material for the preparation of solid electrolytes, have a wide electrochemical window, stable ion transport, and uniform lithium ion deposition, thereby promoting the stable cycle of the battery system.

[0003] With further development and optimization, solid electrolytes can be divided into oxide electrolytes, polymer electrolytes and sulfide electrolytes. Among them, oxide-based ceramics have high mechanical strength, wide electrochemical window and high ionic conductivity, making them easier to prepare on a large scale to meet the requirements of large-size batteries. NASICON-type inorganic electrolytes are a typical oxide electrolyte that has attracted widespread attention due to their stability under ambient conditions, low density, high ionic conductivity and high voltage stability when paired with positive electrodes such as Ni-rich NMC. Although NASICON electrolytes have shown 10 -4 Scm -1 Gao Li + The overall ion conductivity is still not enough to be applied in the development of solid-state batteries. At present, the lithium ion conductivity of solid electrolytes can be effectively improved by adding sintering aids or using special sintering technology and element doping.

[0004] Element doping is an effective method to enhance ionic conductivity by adjusting lattice parameters or controlling bottleneck size. This method is simple to operate and low in cost. Among them, doping with trivalent atoms can produce highly dense NASICON-type ceramic electrolytes. Yttrium (Y) doping can change the structural phase transition temperature of various inorganic compounds by affecting the level of structural distortion. It is reported that Y 3+ Can stabilize Li 1.15 Y 0.15 Zr 1.85 The α phase of (PO4)3(LYZP) makes the total lithium ion conductivity (7×10 -5 S cm -1 ) increased significantly. In addition, using Y 3+ , Gd 3+and Sc 3+ Equivalent ions replace Al 3+ , the ionic conductivity of LAYTP is improved by enhancing the grain boundary bond effect and generating a non-lithium conductive phase. In addition to isovalent doping, microstructure, density and grain size also play a crucial role in ionic conductivity. However, further research is needed to establish the relationship between density, grain size and conductivity. The present invention successfully synthesized Li 1.3 Al 0.3-x Y x Ti 1.7 (PO4)3(LAYTP-x,x=0.00,0.01,0.03,0.05,0.07), explored Y 3+ The influence on the ionic conductivity and chemical stability of ceramic electrolytes. In addition, the present invention comprehensively characterizes the structure, morphology and transport properties of the samples in order to obtain a high-performance solid electrolyte system. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of poor sintering performance and low ion conductivity of existing ceramic solid electrolytes.

[0006] In order to achieve the above object, the first aspect of the present invention provides a NASICON type solid electrolyte, wherein the expression of the NASICON type solid electrolyte is: Li 1.3 Al 0.3-x Y x Ti 1.7 (PO4)3, where 0<x≤0.07.

[0007] Preferably, 0<x≤0.03.

[0008] The second aspect of the present invention provides a method for preparing the NASICON solid electrolyte according to the first aspect of the present invention, the method comprising the following steps:

[0009] (1) weighing a raw material composition, adding it to anhydrous ethanol, performing a first grinding treatment, and then sequentially performing a first drying treatment, a first calcination treatment, a second grinding treatment, and a second drying treatment to obtain LAYTP powder or LATP powder;

[0010] (2) adding PVA to the LAYTP powder or LATP powder, pressing the powder into a disc-shaped green ceramic sheet with a diameter of 12 to 15 mm and a thickness of 1.0 to 1.2 mm, and sequentially performing a sintering treatment and a second calcination treatment on the disc-shaped green ceramic sheet;

[0011] Wherein, in step (1), the raw material composition contains Li source, Al source, Y source, Ti source and P source, and the molar ratio of the Li source calculated as Li element, the Al source calculated as Al element, the Y source calculated as Y element, the Ti source calculated as Ti element and the P source calculated as P element is 1.3:0.3:0.0:1.7:3.0 to 1.3:0.23:0.07:1.7:3.0.

[0012] Preferably, in step (1), the Li source is Li2CO3.

[0013] Further preferably, in step (1), the Al source is Al2O3.

[0014] Preferably, in step (1), the Y source is Y2O3.

[0015] More preferably, in step (1), the Ti source is TiO2.

[0016] Preferably, in step (1), the P source is NH4H2PO4.

[0017] Preferably, in step (1), the amount of anhydrous ethanol used is 30-50 ml relative to the mass of the raw materials of Li source, Al source, Y source, Ti source and P source.

[0018] Further preferably, in step (1), the conditions of the first grinding treatment at least meet the following requirements: a rotation speed of 200 to 400 r / min and a time of 3 to 5 h.

[0019] Preferably, in step (1), the conditions of the first drying treatment at least meet the following requirements: temperature of 80 to 120° C. and time of 5 to 10 h.

[0020] Preferably, in step (1), the conditions of the first calcination treatment at least meet the following requirements: temperature of 700-900° C. and time of 3-5 h.

[0021] Preferably, in step (1), the conditions of the second grinding treatment at least meet the following requirements: a rotation speed of 200 to 400 r / min and a time of 3 to 5 h.

[0022] Preferably, in step (1), the conditions of the second drying treatment at least meet the following requirements: temperature of 80 to 120° C. and time of 5 to 10 h.

[0023] Further preferably, in step (2), the amount of PVA used is 0.07 to 0.1 g relative to 1 g of the LAYTP powder.

[0024] Preferably, in step (2), the sintering treatment conditions at least meet the following requirements: a temperature of 500 to 700° C. and a heat preservation time of 1 to 3 hours.

[0025] Further preferably, in step (2), the conditions of the second calcination treatment at least meet the following requirements: temperature of 800-1000° C. and time of 5-7 h.

[0026] The third aspect of the present invention provides the use of the NASICON solid electrolyte described in the first aspect of the present invention in the preparation of a secondary solid-state lithium battery.

[0027] The NASICON solid electrolyte and the preparation method thereof provided by the present invention also have at least the following beneficial effects:

[0028] The solid electrolytes obtained in the present invention all have a NASICON structure, and the Y element is evenly distributed in the electrolyte. 1.3 Al 0.27 Y 0.03 Ti 1.7 The relative density (95.8%) and total conductivity (2.03×10 -4 S cm -1 ) is the highest, and the income Li 1.3 Al 0.27 Y 0.03 Ti 1.7 The activation energy of (PO4)3 is as low as 0.33 eV. 1.3 Al 0.27 Y 0.03 Ti 1.7 When (PO4)3 is matched with the NCM811 high-voltage cathode, the resulting Li / LAYTP-0.03 / NCM811 battery exhibits excellent electrochemical performance. Specifically, the battery capacity reaches 155 mAh g after 50 cycles at 0.2 °C. -1 The Coulomb efficiency is about 100%, indicating that the Li 1.3 Al 0.27 Y 0.03 Ti 1.7 (PO4)3 electrolyte promotes highly reversible lithium ion insertion / extraction. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is an x-ray diffraction analysis diagram of the NASICON solid electrolyte obtained in Examples 1 to 5 of the present invention;

[0030] Figure 2 is a SEM electron microscope analysis diagram of the NASICON type solid electrolyte obtained in Examples 1 to 5 of the present invention;

[0031] Figure 3 is a relative density analysis comparison diagram of the NASICON solid electrolytes obtained in Examples 1 to 5 of the present invention;

[0032] Figure 4 is an element spectrum analysis diagram of the NASICON solid electrolyte obtained in Example 3 of the present invention;

[0033] Figure 5 is an impedance analysis diagram of the NASICON solid electrolyte obtained in Examples 1 to 5 of the present invention;

[0034] Figure 6 This is an analysis diagram of the ionic conductivity of the NASICON solid electrolyte obtained in Examples 1 to 5 of the present invention as a function of temperature;

[0035] Figure 7 is an analysis diagram of the ionic conductivity of the NASICON solid electrolyte obtained in Examples 1 to 5 as a function of temperature;

[0036] Figure 8 This is the NCM811 / LAYTP-0.03 / Li solid-state battery cycle performance diagram;

[0037] Fig. 9 is the X-ray diffraction analysis diagram of the products obtained in Comparative Example 1 and Comparative Example 2;

[0038] Fig.10 It is the SEM electron microscope analysis picture of the products obtained in Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0039] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0040] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0041] Example 1

[0042] This example is used to provide the preparation of Li 1.3 Al 0.3 Ti 1.7 (PO4)3 method, and the method comprises the following steps:

[0043] (1) Weigh 1.0673 g Li2CO3, 0.309 g Al2O3, 2.722 g TiO2, and 6.9715 g NH4H2PO4, respectively, transfer them to an agate ball mill, add 50 ml anhydrous ethanol, ball mill at 300 r / min for 4 h, dry at 100 °C for 6 h, transfer to 800 °C for calcination for 4 h, and after calcination, grind again at 300 r / min for 3 h, and dry again at 100 °C for 6 h to obtain LATP powder.

[0044] (2) Weigh 10 g of the LATP powder, add PVA, and use a tablet press to press the powder into a disc-shaped green ceramic sheet with a diameter of 15 mm and a thickness of 1.2 mm, and transfer the disc-shaped green ceramic sheet to 600° C. and keep it for 2 hours to remove the added PVA impurities, and then sinter it at 950° C. for 6 hours to obtain a white regular NASICON type solid electrolyte, recorded as LATP; relative to 10 g of the LATP powder, the amount of PVA used is 0.8 g.

[0045] Example 2

[0046] This example is used to provide the preparation of Li 1.3 Al 0.29 Y 0.01 Ti 1.7 (PO4)3 method, and the method comprises the following steps:

[0047] (1) Weigh 1.0673 g Li2CO3, 0.2988 g Al2O3, 0.0226 g Y2O3, 2.722 g TiO2, and 6.9715 g NH4H2PO4, respectively, transfer them to an agate ball mill, add 50 ml anhydrous ethanol, ball mill at 300 r / min for 4 h, dry at 100 °C for 6 h, transfer to 800 °C for calcination for 4 h, and after calcination, grind again at 300 r / min for 3 h, and dry again at 100 °C for 6 h to obtain LAYTP powder.

[0048] (2) Weigh 10 g of the LAYTP powder, add PVA, and use a tablet press to press the powder into a disc-shaped green ceramic sheet with a diameter of 15 mm and a thickness of 1.2 mm, and transfer the disc-shaped green ceramic sheet to 600°C for 2 hours to remove the added PVA impurities, and then sinter at 950°C for 6 hours to obtain a white regular NASICON type solid electrolyte, recorded as LAYTP-0.01; relative to 10 g of the LAYTP powder, the amount of PVA used is 0.8 g.

[0049] Example 3

[0050] This example is used to provide the preparation of Li 1.3 Al0.27 Y 0.03 Ti 1.7 (PO4)3 method, and the method comprises the following steps:

[0051] (1) Weigh 1.0673 g Li2CO3, 0.2781 g Al2O3, 0.0678 g Y2O3, 2.722 g TiO2, and 6.9715 g NH4H2PO4, respectively, transfer them to an agate ball mill, add 50 ml anhydrous ethanol, ball mill at 300 r / min for 4 h, dry at 100 °C for 6 h, transfer to 800 °C for calcination for 4 h, and after calcination, grind again at 300 r / min for 3 h, and dry again at 100 °C for 6 h to obtain LAYTP powder.

[0052] (2) Weigh 10 g of the LAYTP powder, add PVA, and use a tablet press to press the powder into a disc-shaped green ceramic sheet with a diameter of 15 mm and a thickness of 1.2 mm, and transfer the disc-shaped green ceramic sheet to 600°C for 2 hours to remove the added PVA impurities, and then sinter at 950°C for 6 hours to obtain a white regular NASICON type solid electrolyte, recorded as LAYTP-0.03; relative to 10 g of the LAYTP powder, the amount of PVA used is 0.8 g.

[0053] Example 4

[0054] This example is used to provide the preparation of Li 1.3 Al 0.25 Y 0.05 Ti 1.7 (PO4)3 method, and the method comprises the following steps:

[0055] (1) Weigh 1.0673 g Li2CO3, 0.2575 g Al2O3, 0.113 g Y2O3, 2.722 g TiO2, and 6.9715 g NH4H2PO4, respectively, transfer them to an agate ball mill, add 50 ml anhydrous ethanol, ball mill at 300 r / min for 4 h, dry at 100 °C for 6 h, transfer to 800 °C for calcination for 4 h, and after calcination, grind again at 300 r / min for 3 h, and dry again at 100 °C for 6 h to obtain LAYTP powder.

[0056] (2) Weigh 10 g of the LAYTP powder, add PVA, and use a tablet press to press the powder into a disc-shaped green ceramic sheet with a diameter of 15 mm and a thickness of 1.2 mm, and transfer the disc-shaped green ceramic sheet to 600°C for 2 hours to remove the added PVA impurities, and then sinter at 950°C for 6 hours to obtain a white regular NASICON type solid electrolyte, recorded as LAYTP-0.05; relative to 10 g of the LAYTP powder, the amount of PVA used is 0.8 g.

[0057] Example 5

[0058] This example is used to provide the preparation of Li 1.3 Al 0.23 Y 0.07 Ti 1.7 (PO4)3 method, and the method comprises the following steps:

[0059] (1) Weigh 1.0673 g Li2CO3, 0.2575 g Al2O3, 0.1582 g Y2O3, 2.722 g TiO2, and 6.9715 g NH4H2PO4, respectively, transfer them to an agate ball mill, add 50 ml anhydrous ethanol, ball mill at 300 r / min for 4 h, dry at 100 °C for 6 h, transfer to 800 °C for calcination for 4 h, and after calcination, grind again at 300 r / min for 3 h, and dry again at 100 °C for 6 h to obtain LAYTP powder.

[0060] (2) Weigh 10 g of the LAYTP powder, add PVA, and use a tablet press to press the powder into a disc-shaped green ceramic sheet with a diameter of 15 mm and a thickness of 1.2 mm, and transfer the disc-shaped green ceramic sheet to 600°C for 2 hours to remove the added PVA impurities, and then sinter at 950°C for 6 hours to obtain a white regular NASICON type solid electrolyte, recorded as LAYTP-0.07; relative to 10 g of the LAYTP powder, the amount of PVA used is 0.8 g.

[0061] Comparative Example 1

[0062] This example is carried out according to the method of Example 1, except that in step (2), the disc-shaped green ceramic sheet is sintered at 950° C. for 4 hours. The remaining steps and parameters are the same as those of Example 1.

[0063] Comparative Example 2

[0064] This example is carried out according to the method of Example 1, except that in step (2), the disc-shaped green ceramic sheet is sintered at 950° C. for 8 hours. The remaining steps and parameters are the same as those of Example 1.

[0065] Test Example 1

[0066] The NASICON solid electrolytes obtained in Examples 1 to 5 were subjected to X-ray diffraction analysis. The results are as follows: Figure 1 As shown; and the products obtained in Comparative Example 1 and Comparative Example 2 were subjected to X-ray diffraction analysis, and the results were as follows Fig. 9 shown.

[0067] Depend on Figure 1 It can be seen that the diffraction peaks of the NASICON-type solid electrolytes obtained in Examples 1 to 5 of the present invention all conform to the characteristic peaks of the NASICON-type LTP (PDF#35-0754). In addition, the peak intensity and peak width of the obtained NASICON-type solid electrolytes remain consistent, indicating that Y 3+ The addition of has no effect on the structural composition of LAYTP. In addition, impurity phases such as LiTiPO5 were observed in the XRD pattern, which may be caused by the loss of lithium salt volatilization during sintering, the decomposition of LAYTP phase or the uneven mixing of raw materials.

[0068] Depend on Fig. 9 It can be seen that the diffraction peaks of the LATP ceramic electrolyte obtained in Comparative Examples 1 and 2 of the present invention conform to the characteristic peaks of NASICON-type LTP (PDF#35-0754). In addition, the peak intensity and peak width of the LATP electrolyte obtained in Comparative Example 1 remain consistent, indicating that when the sintering temperature is 950°C and the temperature is kept for 4 hours, a pure phase LATP ceramic electrolyte can be obtained. However, impurity phases such as LiTiPO5 can be clearly observed in the LATP electrolyte obtained in Comparative Example 2, which may be caused by the long sintering time, the lack of lithium salt volatilization, the decomposition of the LAYTP phase, or the uneven mixing of the raw materials.

[0069] Test Example 2

[0070] The NASICON solid electrolytes obtained in Examples 1 to 5 were analyzed by SEM electron microscope. Figure 2 As shown; and the products obtained in Comparative Example 1 and Comparative Example 2 were subjected to SEM electron microscope analysis, and the results were as follows Fig.10 shown.

[0071] Depend on Figure 2 It can be seen that the NASICON solid electrolytes obtained in Examples 1 to 5 of the present invention are 3+ As the amount of addition increases, the number of rectangular grains increases and the grain structure becomes denser. The grain size increases first and then gradually tends to be balanced. The increase in grain size can effectively reduce the generation of grain boundaries and defects, and ultimately improve the density and electrochemical properties of LAYTP ceramics.

[0072] Depend on Fig.10It can be seen that the NASICON-type solid electrolytes obtained in Comparative Examples 1 and 2 of the present invention both exhibit NASICON-type block-shaped grain structures. Moreover, the LATP electrolyte obtained in Comparative Example 1 has a dense surface, but the grain size difference is obvious, indicating that when the sintering temperature is 950°C and the insulation is 4h, the ceramic does not achieve the best sintering effect. In addition, the grain size of the LATP electrolyte obtained in Comparative Example 2 is larger, but the voids at the grain boundaries are more obvious, indicating that when the sintering temperature is 950°C and the insulation is 8h, the ceramic is over-burned, which ultimately affects the electrochemical properties of the electrolyte. The above results show that in order to obtain a LATP ceramic electrolyte system with excellent performance, while ensuring the density of the electrolyte, the grain size and uniformity are also very important.

[0073] Test Example 3

[0074] The relative density analysis of the NASICON solid electrolytes obtained in Examples 1 to 5 was performed, and the results were as follows: Figure 3 shown.

[0075] Depend on Figure 3 It can be seen that the NASICON solid electrolytes obtained in Examples 1 to 5 of the present invention have a larger grain size, and the relative density of the ceramic samples increases from 90.3% of LAYTP to 95.8% of LAYTP-0.03; 3+ With further increase of content (x = 0.05 and 0.07), the relative density decreases slightly to 92.5% and 93%, respectively, which may be due to the formation of excessive LiTiPO5 impurity phase on the grain boundary. Nevertheless, all samples show a high relative density (> 92%), indicating that LAYTP-x ceramics are well sintered, which is beneficial to improve the conductivity.

[0076] Test Example 4

[0077] The NASICON solid electrolyte obtained in Example 3 was subjected to elemental spectrum analysis, and the results were as follows: Figure 4 shown.

[0078] Depend on Figure 4 It can be seen that the element spectrum of the NASICON solid electrolyte obtained in Example 3 of the present invention shows the uniform distribution of the Y element in the electrolyte region.

[0079] Test Example 5

[0080] The NASICON solid electrolytes obtained in Examples 1 to 5 were subjected to impedance analysis. The results are as follows: Figure 5 shown.

[0081] Depend on Figure 5 It can be seen that the NASICON solid electrolytes obtained in Examples 1 to 5 of the present invention have3+ When the doping amount of LAYTP is 0-0.03, the total impedance of LAYTP solid electrolyte is significantly reduced. Since LAYTP-0.03 has the highest relative density (95.8%), this sample exhibits the smallest total impedance value: 7.28×10 2 Ω. At the same time, the sample has the highest ionic conductivity: 2.03×10 -4 S cm -1 As mentioned above, Y 3+ The addition of significantly improved the sintering properties of LAYTP, thereby increasing the relative density of LAYTP and further improving the ionic conductivity of LAYTP.

[0082] Test Example 6

[0083] The NASICON solid electrolytes obtained in Examples 1 to 5 were subjected to an analysis of the ionic conductivity as a function of temperature (25 to 70° C.). The results are as follows: Figure 6 As shown, according to the Arrhenius formula, the activation energies of the NASICON solid electrolytes obtained in Examples 1 to 5 are calculated to be 0.38 eV, 0.30 eV, 0.33 eV, 0.35 eV and 0.41 eV, respectively.

[0084] Test Example 7

[0085] The NASICON solid electrolytes obtained in Examples 1 to 5 were subjected to an analysis of the ionic conductivity as a function of temperature (25 to 70° C.). The results are as follows: Figure 7 As shown,

[0086] Figure 7 The ionic conductivity and activation energy of the NASICON solid electrolytes obtained in Examples 1 to 5 were analyzed. As can be seen from the figure, the obtained LAYTP-0.03 has the highest ionic conductivity and the lowest activation energy, indicating that the appropriate amount of Y 3+ Doping can reduce the ion diffusion energy barrier, obtain lower activation energy, and thus improve the ionic conductivity of the electrolyte.

[0087] Test Example 8

[0088] The LAYTP-0.03 obtained in Example 3 was used as the electrolyte, and a commercial 2032 battery shell, a commercial NCM811 positive electrode, a separator and a metal lithium negative electrode were used as quasi-solid-state battery assembly materials.

[0089] Specifically, the positive electrode is composed of 80wt% NCM811 powder, 10wt% Super-P, and 10wt% PVDF binder. The above positive electrode materials are added to N-methylpyrrolidone to obtain a viscous slurry, which is then coated on aluminum foil and dried overnight at 80°C under vacuum. The electrode is punched with a diameter of 12mm and the active material loading is controlled to 2-3mg / cm 2 The entire battery assembly process was carried out in a glove box filled with Ar (O2<5ppm, H2O<5ppm), where about 5μL of commercial electrolyte (1.0MLiPF6 / EC-DEC (1:1vol / vol) was added to reduce the interfacial contact resistance between the electrolyte and the positive electrode. In addition, in order to prevent the LAYTP electrolyte from being reduced by lithium metal, a layer of Celgard 2400 diaphragm soaked in commercial electrolyte was added.

[0090] Figure 8 The LAYTP-0.03 obtained in Example 3 is used as the electrolyte, matched with the high-voltage NCM811 positive electrode, and assembled into NCM811 / LAYTP-0.03 / Li solid-state battery cycle performance. Figure 8 It can be seen that the solid-state battery can obtain 155mAh g at a current density of 0.2C at room temperature. -1 The initial specific capacity is 100%, and after 50 stable cycles, the Coulombic efficiency is still close to 100%, showing excellent electrochemical performance, indicating that the LAYTP-0.03 electrolyte prepared by the present invention can achieve stable lithium ion transport, thereby obtaining an excellent high-voltage solid-state battery system.

[0091] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A NASICON type solid electrolyte, characterized in that: The expression of the NASICON solid electrolyte is: Li 1.3 Al 0.3-x Y x Ti 1.7 (PO4)3, where 0<x≤0.

07.

2. The solid electrolyte according to claim 1, wherein 0<x≤0.03。 3. A method for preparing a NASICON solid electrolyte as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: (1) weighing a raw material composition, adding it to anhydrous ethanol, performing a first grinding treatment, and then sequentially performing a first drying treatment, a first calcination treatment, a second grinding treatment, and a second drying treatment to obtain LAYTP powder or LATP powder; (2) adding PVA to the LAYTP powder or LATP powder, pressing the powder into a disc-shaped green ceramic sheet with a diameter of 12 to 15 mm and a thickness of 1.0 to 1.2 mm, and sequentially performing a sintering treatment and a second calcination treatment on the disc-shaped green ceramic sheet; Wherein, in step (1), the raw material composition contains Li source, Al source, Y source, Ti source and P source, and the molar ratio of the Li source calculated as Li element, the Al source calculated as Al element, the Y source calculated as Y element, the Ti source calculated as Ti element and the P source calculated as P element is 1.3:0.3:0.0:1.7:3.0 to 1.3:0.23:0.07:1.7:3.

0.

4. The method according to claim 3, wherein: In step (1), the Li source is Li2CO3; And / or, in step (1), the Al source is Al2O3; And / or, in step (1), the Y source is Y2O3; And / or, in step (1), the Ti source is TiO2; And / or, in step (1), the P source is NH4H2PO4.

5. The method according to claim 3 or 4, wherein: In step (1), the amount of anhydrous ethanol used is 30-50 ml relative to the mass of the raw materials of Li source, Al source, Y source, Ti source and P source; And / or, in step (1), the conditions of the first grinding treatment at least meet the following conditions: a rotation speed of 200 to 400 r / min and a time of 3 to 5 h; And / or, in step (1), the conditions of the first drying treatment at least meet the following conditions: temperature of 80 to 120° C. and time of 5 to 10 h; And / or, in step (1), the conditions of the first calcination treatment at least meet the following conditions: temperature of 700-900° C. and time of 3-5 h; And / or, in step (1), the conditions of the second grinding treatment at least meet the following conditions: a rotation speed of 200 to 400 r / min and a time of 3 to 5 h; And / or, in step (1), the conditions of the second drying treatment at least meet the following requirements: temperature of 80 to 120° C. and time of 5 to 10 hours.

6. The method according to claim 3 or 4, wherein: In step (2), the amount of PVA used is 0.07 to 0.1 g relative to 1 g of the LAYTP powder.

7. The method according to claim 3 or 4, wherein: In step (2), the sintering treatment conditions at least meet the following requirements: temperature of 500-700° C. and holding time of 1-3 h; And / or, in step (2), the conditions of the second calcination treatment at least meet: a temperature of 800 to 1000° C. and a time of 5 to 7 hours.

8. Use of the NASICON solid electrolyte according to claim 1 or 2 in the preparation of a secondary solid-state lithium battery.